Heavy metal in fish: analysis and human health - a review - Azaman, Fazureen; Juahir, Hafizan; Azid, Azman; Yunus, Kamaruzzaman; Kamarudin, Mohd Khairul Amri; Toriman, Mohd Ekhwan; Mustafa, Ahmad Dasuki; Amran, Mohammad Azizi; Che Hasnam, Che Noraini; Mohd Saudi, Ahmad Shakir (Universiti Teknologi Malaysia, 2015)
Living organisms require trace amounts of heavy metals, including cobalt, copper, manganese and zinc to survive. However, the excessive levels of the metal can be detrimental to the organism. Other heavy metals such as mercury, lead and cadmium have no vital on organisms, and their accumulation in long time period in the bodies can cause serious illness or death. The consumption of fish is recommended because fish is a basic and good nutritious food that has omega-3 fatty acids due to its cardio-protective effects. This present mini-review accounts for the description of heavy metal in fish and the effect of toxic metals on the human health. Besides, the acid digestion method was also discussed in order to identify the best method for applying in the laboratory analysis. The best method used can reduce the contamination error in the results.